Crystallization of novel ARM lipase and elucidation of its space-grown crystal structure - Nisbar, Nur Dayana (2013)
The three-dimensional structure of novel thermostable and organic solvent tolerant ARM lipases was successfully determined by X-ray crystallography technique. The novel ARM lipase was highly purified prior to crystallization and consequently, the crystal structure of ARM lipase was elucidated in order to comprehend its structurefunction relationship. The His-tagged ARM lipase was purified using immobilized metal affinity chromatography followed by anion-exchange chromatography. The highly purified and homogeneous ARM lipase with protein concentration of approximately 2 mg/mL was successfully crystallized by sitting drop, vapour diffusion method using 0.1 M MES monohydrate pH 6.5 and 12% (v/v) polyethylene glycol (PEG) 20000 as precipitant. Optimization of the crystallization conditions was performed by varying the pH and concentration of the precipitant. The optimum crystallization condition was 2 mg/mL ARM lipase in 0.1 M Tris-HCl, 0.15 M NaCl, pH 8.0 protein solution,crystallized using 0.1 M Tris-HCl, pH 8.0 and 12% (v/v) PEG 20000 as precipitant. In addition, the crystal growth of ARM lipase was also improved via counter diffusion method and microgravity experiment. Crystals grew in the gel-tube capillaries that are incubated in Protein Crystallization Research Facility on board the International Space Station for over three months in 2011. The space-grown crystal obtained was diffracted and data was collected at synchrotron radiation facility. The data was processed up to 2.3 Å resolution and the crystal belonged to primitive monoclinic P21 space group with the unit cell dimension of a= 55.79 Å, b=143.40 Å, c=63.97 Å, α=γ=90.00° and β= 105.88°. Crystal structure of ARM lipase showed the typical, canonical alpha-beta hydrolase fold consisting of 13 α-helices and 11 β-strands. The conserved catalytic triad, composed of serine 113, histidine 358 and aspartic acid 317 was found in the hydrophobic active site. Three-dimensional structure features such as zinc- and calcium-binding sites, high percentage of charged, aromatic and proline residues presence in the protein, as well as high percentage of surface-exposed charged,hydrophobic and glycine residues explains the properties of ARM lipase as a thermostable, organic solvent- stable lipase. In conclusion, the successful crystallization and structure elucidation of novel thermostable, organic solvent-tolerant lipase, ARM gives an understanding of the properties of this enzyme. Information regarding the structural features and adaptations of this lipase also gives useful insight for the engineering of better, novel lipases with enhanced and desired properties.